Inventors emerging in-school and out-of-school: six iterations of educational design to promote equitable student engagement - Jackson, David W.; Zhang, Helen; Asante, Christian K.; Semerjian, Amy R.; Barnett, G. Michael; Couch, Stephanie; Estabrooks, Leigh; Kiel, Jeffrey; Kulkarni, Neema (Frontiers in Education, 2024)
Invention education is an emerging field that shows promise for fostering equitable student engagement, especially related to disciplines of science, technology, engineering, arts, and mathematics (STEAM), in both classroom and informal learning. A central concept for practitioners, researchers, and evaluators, student engagement connects with academic, socioemotional, career, and civic success. Nonetheless, more work is needed to ensure more equitable approaches to educational design for student engagement, especially with youth of one or more minoritized identity markers (e.g., Black, brown, or indigenous youth; female or non-binary youth; youth from lower socioeconomic statuses; etc.). This Curriculum, Instruction, and Pedagogy article describes six iterations of educational designs for invention education with grades 6-8 classes and camps. Three of the iterations revised the same curriculum for grade 7 classes (N 160 students/year), and the other three iterations involved similar yet distinct curricula for grades 6-8 camps (N 25 students/year). Taking a cultural psychology approach to design-based research, we conducted a phenomenological mixed-methods study for convergence. That is, we iteratively refined educational designs within given microcultures, and we sought to better understand participants' lived experiences. We share evidence of high affective, behavioral, and cognitive engagement, within and between both individual and social levels, alongside development of self-efficacy with respect to ability beliefs and anxiety management. With a few exceptions, our findings suggest equitable participation of youth. These findings we connect with educational design considerations, including individual-vs.-social supports, explicit attention to youths' hobbies and peer-inventors, and formative assessment that broadens response scales and gradations of challenge. Our work supports a more nuanced and socially-situated six-dimensional framework for student engagement, expanding upon commonlyused three-and four-dimensional models. We conclude with local and transferrable implications, towards the main goal of fostering equitable student engagement in science and engineering through invention education.